Online harmonic extraction and synchronization algorithm based control for unified power quality conditioner for microgrid systems - Hasan K.; Othman M.M.; Meraj S.T.; Rahman N.F.A.; Noor S.Z.M.; Musirin I.; Abidin I.Z. (Elsevier Ltd, 2023)
Adaptive control systems; Battery storage; Microgrids; Online systems; Power quality; Quality control; Solar power generation; Adaptive linear neural network; Battery energy storage; Critical load; Harmonic extraction; Microgrid; Neural network based control; Neural-networks; Power quality problem; Solar photovoltaics; Unified power quality conditioners; MATLAB